Milli Mücadele Dönemi ve Cumhuriyet Yönetimine Geçişte Türk Hariciye Teşkilatı’nın Gelişimi - Resul YAVUZ (Gazi Akademik Bakış)
The Turkish Foreign Office, which was shaped by the accumulation of a long history, adopted a new legacy to the New Turkish State with the adoption of western standards during the modernization period. However, it was possible for this legacy to go through a long and arduous process to contribute to the visionary structure of the state by reassessing it in the hands of the Turkish Grand National Assembly while the War of Independence was going on in Anatolia. While the state institutions were re-established with the opening of the Turkish Grand National Assembly in Ankara, the Foreign Service started its activities in a small place devoted to it, and in time it grew and gained its institutional structure. Working with a small staff in Anatolia, where the war continued with all its violence, the Foreign Service made a great contribution to the victory of this process by conducting the diplomatic network of the National Struggle with the representatives it opened in Moscow, Baku, Tbilisi, Paris and Rome. The support provided by the Foreign Office, which has recently started to be organized, especially during the stages of conferences and agreements, has facilitated the work of the Turkish Grand National Assembly on one hand and made a significant contribution to the victory of the struggle on the front desk on the other hand. After the end of this difficult period and the proclamation of the Republic, the Turkish Foreign Office has also taken many steps to improve its institutional structure professionally. In this period, while overseas organizations were given great importance, efforts were made to establish the cadre structure as required by the era.